2019
DOI: 10.1088/1361-6382/ab4cd3
|View full text |Cite
|
Sign up to set email alerts
|

All superalgebras for warped AdS 2 and black hole near horizon geometries

Abstract: We identify all symmetry superalgebras g of near horizon geometries of black holes with a Killing horizon, assuming the solution is smooth and that the spatial cross section of the event horizon is compact without boundary. This includes all warped AdS 2 backgrounds with the most general allowed fluxes in 10-and 11dimensional supergravities. If the index of a particular Dirac operator vanishes, we find that the even symmetry subalgebra decomposes as g 0 = sl(2, R)⊕ t 0 , where t 0 /c is the Lie algebra of a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…The geometric structure of near-horizon solutions admitting N = 2 JHEP07(2021)155 supersymmetry was classified in [25,26]. Following on from this, analysis of the superalgebras associated with supersymmetric near-horizon geometries [27,28] was used to further elucidate the nature of the symmetry algebras of solutions with N > 2 supersymmetry. In conjunction with the homogeneity theorem in [29], together with a classification of all compact homogeneous 9-dimensional Riemannian manifolds in [30], it was shown that there are no supersymmetric near horizon geometries with 16 < N < 32 supersymmetries.…”
Section: Jhep07(2021)155mentioning
confidence: 99%
See 2 more Smart Citations
“…The geometric structure of near-horizon solutions admitting N = 2 JHEP07(2021)155 supersymmetry was classified in [25,26]. Following on from this, analysis of the superalgebras associated with supersymmetric near-horizon geometries [27,28] was used to further elucidate the nature of the symmetry algebras of solutions with N > 2 supersymmetry. In conjunction with the homogeneity theorem in [29], together with a classification of all compact homogeneous 9-dimensional Riemannian manifolds in [30], it was shown that there are no supersymmetric near horizon geometries with 16 < N < 32 supersymmetries.…”
Section: Jhep07(2021)155mentioning
confidence: 99%
“…In this section, we collate and summarize the key results obtained from [25][26][27][28]37], which we shall utilize in considering the analysis of near-horizon geometries.…”
Section: Supersymmetric Near-horizon Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…One uses a similar methodology to establish the classification statement for AdS 4 backgrounds in Section 12.7 for (massive) IIA and IIB supergravities. This method can also be extended to prove a non-existence result for AdS 2 and AdS 3 backgrounds that preserve N > 16 supersymmetries [261,265].…”
Section: A Non-existence Theorem For Warped N = 24 Ads 5 Backgroundsmentioning
confidence: 99%
“…It has also been shown in [18] that the only smooth AdS 4 solution with compact without boundary internal space that preserves 16 < N < 32 supersymmetries is locally isometric to the N = 24 IIA solution AdS 4 × CP 3 of [19]. Moreover it has been shown in [20] that there are no smooth AdS 2 backgrounds in 10-and 11-dimensional supergravities with compact without boundary internal space that preserve N > 16 supersymmetries. Product solutions AdS n × M D−n with M D−n a symmetric space have been classified in [21]- [24].…”
Section: Introductionmentioning
confidence: 99%